Decoupling of hyperfine structure of Cs D1 line in strong magnetic field studied by selective reflection from a nanocell; Journal of the Optical Society of America B; Vol. 34, iss. 4 - Sargsyan A. D. Armen; Klinger E. Emmanuel; Hakhumyan G. T. Grant; Tonoyan A. Ara; Papoyan A. Aram; Leroy K. A. Klod (Claude) Andre; Sarkisyan D. H. David (2017, 2017)
Title screen